Implementasi Low Power Wireless Sensor Network Untuk Pengukuran Suhu Berbasis NRF Dengan Penjadwalan Pengiriman Data - Ahmad Faris Adhnaufal; Sabriansyah Rizqika Akbar; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
The needs of an extended time of observation monitoring in a remote location without suffice energy resource to accommodate has become the challenge of the future development of wireless sensor node. Wireless sensor node can deploy more than 1 unit in the remote area. So there must be a method to arrange a schedule of data delivery from the node to base station. So this research conducts to configure a time scheduling for data sending and sleepy low power mode to more than 1 node to make it compatible without affecting the system. Researcher applying a low power mode that using the Jeelib library that have been approved to lowering current usage in Arduino microcontroller for almost 14.5 mA at sensor reading phase, 11.2 mA at data sending phase, 14.3 mA at idle phase. Then the next part is to configure low power mode with compatible Time Division Multiple Access (TDMA) so the node can have a fix schedule about their phase. After the research, the result came that the clock time in the node can synchronized with the base station using Timing-sync Protocol for Network (TPSN) algorithm method in 30 seconds average of synchronization process. The node gets a fix schedule for data sending phase for each and low power mode kick in the microcontroller to sleep until next data sending phase without affecting the system works.